2023
DOI: 10.1002/aenm.202303705
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Silicon Solar Cells through Organic Self‐Assembled Monolayers as Electron Selective Contacts

Adi Prasetio,
Rakesh R. Pradhan,
Pia Dally
et al.

Abstract: Effective charge carrier‐selective contacts are a crucial component of high‐performance crystalline silicon (c‐Si) solar cells. Organic materials deposited via self‐assembly on the c‐Si surface are promising candidates for simplified, scalable, and cost‐effective processing of charge extraction layers. This study investigates the application of nPACz self‐assembled monolayers (SAMs), based on carbazole and phosphonic acid groups, where n (= 2, 4, or 6) is the aliphatic chain length, to facilitate electron extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The WF of ITO/ PANDI (∼4.45 eV) is found to be lower than that of ITO/ PAAQ (∼4.66 eV), indicating a more favorable energetic alignment for electron extraction. Therefore, the larger WF difference of ITO/ PANDI (∼0.27 eV) than ITO/ PAAQ (∼0.10 eV), in reference to bare-ITO, enhances the band bending at the ITO/ PANDI /perovskite interface, thereby improving its electron selectivity (see also the schematic illustration in Figure c). , The larger shift of the WF of PANDI can be associated with its larger interface dipole compared to PAAQ , as discussed above. Apart from WF modifications, the SAM coatings do not significantly change the surface roughness of ITO, as shown by AFM results in Figure S13.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The WF of ITO/ PANDI (∼4.45 eV) is found to be lower than that of ITO/ PAAQ (∼4.66 eV), indicating a more favorable energetic alignment for electron extraction. Therefore, the larger WF difference of ITO/ PANDI (∼0.27 eV) than ITO/ PAAQ (∼0.10 eV), in reference to bare-ITO, enhances the band bending at the ITO/ PANDI /perovskite interface, thereby improving its electron selectivity (see also the schematic illustration in Figure c). , The larger shift of the WF of PANDI can be associated with its larger interface dipole compared to PAAQ , as discussed above. Apart from WF modifications, the SAM coatings do not significantly change the surface roughness of ITO, as shown by AFM results in Figure S13.…”
mentioning
confidence: 92%
“…Accordingly, we found that the net dipole moment of PAAQ at 3.94 D is smaller than that of PANDI (4.58 D). However, it is crucial to acknowledge that the net dipole moments of SAM molecules may not linearly follow the WF values, as the orientation and packing of the SAMs with respect to the ITO surface is still not fully understood. , Nevertheless, by assuming the perpendicular orientation of the SAM molecules to the substrates, the z -projection of the dipole moment becomes particularly relevant, given its higher contribution compared to the x - and y -projections. Upon calculation, we found that the z -projection dipole moment values for PAAQ and PANDI are −0.20 and −1.04 D, respectively (Figure S11 and Table S2).…”
mentioning
confidence: 99%